Online education and digital transformation in priestly formation: challenges and opportunities in the technological era: Online education and digital transformation in priestly - Freire Menoscal, Stalyn (Revista Ecos de la Academia, 2025)
This article examines the implementation of online education in priestly formation, analyzing its challenges and opportunities in the digital era. The study was conducted in three houses of priestly formation in Ecuador, using a mixed method that included surveys and interviews with 38 participants (30 students and 8 teachers). The results showed a positive impact of the digital platform on the learning experience (M=4.13), with a strong correlation between the use of digital resources and the quality of learning (r=0.75). The research identified significant benefits in terms of accessibility to theological resources, flexibility in learning and improved communication between teachers and students. However, it also revealed significant challenges, especially in the development of specific digital competencies, where the lowest scores were obtained (M=3.78). The study highlights the importance of complementing spiritual training with practical skills for community development, including aspects of agriculture, local economy and language. The findings suggest that a hybrid model combining face-to-face and virtual elements could be the most effective for modern priestly formation.